Long-term stability of an anterior open-bite malocclusion treated in the mixed dentition: a case report Estabilidade a longo prazo do tratamento da mordida aberta anterior na dentadura mista: relato de caso clínico - Márcio Rodrigues de Almeida; Renato Rodrigues de Almeida; Ana Claúdia de Castro Ferreira Conti; Ricardo de Lima Navarro; Giovani de Oliveira Correa; Cristiane Aparecida de Oliveira; Paula Vanessa Pedron Oltramari (University of São Paulo, 2006)
A clinical case with anterior open-bite, treated in the mixed dentition, is presented. This approach demonstrates one of the possible approaches of treatment, which is capable of interfering with growth and redirecting its vectors. Orthodontic and orthopedic methods were used, consisting of slow maxillary expansion, through a fixed palatal crib soldered in a bi-helix appliance, and high-pull traction on the mandible for 16 hours a day. After eight years of follow-up, stable outcomes were accomplished. These results may be explained by the fact that treatments were performed at the appropriate period of development, thus establishing perioral muscular equilibrium, matching the final period of facial growth. The combination of orthodontic and orthopedic treatments was necessary to prevent the need of further orthognathic surgery treatment. Apresentou-se um relato de caso clínico de mordida aberta anterior, tratada em dentadura mista, demonstrando uma das possíveis formas de tratamento, capaz de interferir no crescimento e redirecionar seus vetores. Os protocolos ortodônticos e ortopédicos utilizados foram a expansão lenta da maxila, utilizando grade palatina soldada a um expansor bihélice, com tração alta na mandíbula, num período diário de 16 horas. Oito anos de estabilidade foram alcançados, explicados pelo fato de o tratamento ter sido conduzido no momento oportuno do desenvolvimento, o que estabeleceu equilíbrio entre os músculos peribucais, em conjunto com o período final do crescimento. A combinação do tratamento ortodôntico e ortopédico foi necessária para se evitar a necessidade de tratamento cirúrgico.